Where to eat: exploring silver consumer restaurant dining choice in Malaysia - Abu Bakar, Ainul Zakiah; Ganesan, Lalitha; Othman, Mohhidin; Haron, Sharifah Azizah; Che Ishak, Farah Adibah (Universiti Putra Malaysia Press, 2020)
Eating out among older adults are becoming the norm due to its convenience and potential for social interaction. Malaysia is expected to become an aged nation whereby 14% or more of its population will be 65 years and older by 2050. Very little is known about restaurant preferences and patronage behaviours of older adults in Malaysia even though there had been numerous researches done involving this population. It is important to acknowledge this age group not just because they are living longer; but also, because they are getting bigger in size and economic power. The purpose of this study is to determine the factors influencing Malaysian older or silver consumers’ restaurant dining choices. Semistructured in-depth interviews were done with Malaysian older people ages 55 and above. The interviews were recorded, transcribed and analysed. Atlas.ti software (version 7) was used to complement researchers’ analyses of interview transcripts and develop a visual representation of qualitative data. Major thematic categories identified by older consumers in this study included food, service, and location. Data are visually mapped and relationships between different themes are presented. This study will be beneficial in providing more insights to restaurateurs in Malaysia to better meet silver consumer needs.